The mediation role of work environment in the relationship between occupational hygiene practices and the health and safety of waste scavengers in emerging economies - Cyrus N. Younquoi; Best Ordinioha; Mosoka P. Fallah (Discover Environment)
Abstract Due to the high unemployment rate in Liberia, many individuals engage in waste scavenging as a means of survival. These scavengers are exposed to various hazards, including infections, respiratory illnesses, and accidents, often operating in unsafe environments without protective equipment. This study applied the Job Demands-Resources (JD-R) Theory to examine how the work environment mediates the relationship between occupational hygiene practices and health and safety among waste scavengers. The sample size was determined using Cochran’s formula for an unknown population, and data were collected from 384 waste scavengers in Liberia through snowball sampling. Partial Least Squares Structural Equation Modeling (PLS-SEM), specifically the bootstrapping method, was employed to analyze the data and evaluate both measurement and structural models. The results showed that occupational hygiene practices have a significant positive effect on both health and safety and the work environment. Additionally, the work environment was found to partially mediate the relationship between occupational hygiene practices and health and safety. The study recommends that the government implement regulations to ensure safe working conditions for waste scavengers. These policies should require waste management companies to adopt appropriate hygiene standards, safeguard the environment, and follow proper waste disposal protocols.